Pusat Jajanan Serba Ada (Pujasera) Dengan Pendekatan Arsitektur Tepian Air - Muhammad Iqbal; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Food Center Departement Stores (Food Court) in Rokan Hulu is the only one center of the culinary tourism in Rokan Hulu. Culinary activities covered by the existing facilities in the design that is supported by views freely toward the waterfront area, namely Sungai Batang Lubuh. Through the concept of Eddies Flow design food court at the center of culinary tourism in Rokan Hulu can realize the main function of the design to be the center of culinary tourism in Rokan Hulu utilizing the potential of local wisdom in the surrounding waterfront area to be the development of the design using the response and approach application of Waterfront Architecture.keywords : Rokan Hulu, Food Court, Waterfront Architecture.